Formulation, Characterization and in vivo Evaluation of 5-Fluorouracil-Loaded Polymeric Micelles for Non-Melanoma Skin Cancer - Mehan, Navneet; Saini, Vipin; Manish, Kumar; Goyal, Manoj; Devi, Sheetal; Pottathil, Shinu; Jacob, Shery; Nair, Anroop B (Indian Journal of Pharmaceutical Education and Research, 2025)
Background The goal of the study was to evaluate the prospective of fluorouracil-loaded polymeric micelles for topical delivery in non-melanoma skin cancer. Materials and Methods Polymeric micelles were developed by thin film hydration technique and characterized for physico-chemical properties, in vitro drug release, ex vivo skin penetration as well as in vivo skin irritation and anticancer effect. Results Preliminary studies were carried out in twelve Formulations (FM1-FM12) and the Formulation (FM4) with the highest entrapment efficiency (~95%) and greater drug release (~98%) was developed into gels (FG1-FG5). The selected gel Formulation (FG4) exhibited adequate viscosity (~5000 cP), ideal pH (~6.8), higher drug content (~79%), greater drug permeation (~70%) and good stability for three months. In vivo skin irritation results indicated the developed formulation is non-irritant. MTT assay indicates dose-dependent effect of FG4 with IC50 of 15.56 μg/mL. Anti-cancer activity assessed in rat models indicates the prominent reduction in tumor burden (volume) by 80% following application of fluorouracil-loaded micellar gel for 1 month. The histopathological study further confirms the activity of developed gel in melanoma skin cancer. Conclusion The data observed suggests that the polymeric micelles could be a feasible option for delivering fluorouracil in the treatment of basal-cell carcinoma.
Keywords: Drug release; Fluorouracil; Polymeric micelles; Rats; Skin carcinoma.